Apical patency as a way of preserving the apical third area of endodontic treatment - Juni Jekti Nugroho; Aisyah Pertiwi Utami (Makassar Dental Journal, 2020)
Introduction: The apical third of the root canal system is very complex portion and challenging during endodontic treatment. Blockage of the root canal in the apical region by remnants of hard tissue and soft tissue debris, may cause procedural errors such as apical transportations, ledge and perforation. These debris contain bacteria inducing periradicular disease. The apical patency technique is considered as a way for maintaining the apical part free of debris by recapitulation using a small K-file through the apical foramen to assure that the canal system is predictably negotiable. Aim: To review the significance of apical patency as one of clinical approaches to reduce treatment failure on endodontic therapy. Conclusion: Apical patency may im-prove the result of cleaning procedure, for both mechanically and biologically way, in apical third area of canal system.